From Frustrating Data Experiences to Anti-Privacy Attitudes: A Healthcare Case Study - Shaul A Duke (Surveillance & Society, 2026)
Although the GDPR and other privacy-protecting measures in healthcare are deemed beneficial and necessary (albeit not sufficient) by surveillance and privacy scholars, it seems they have also gathered opposition among some of the ordinary people who nowadays interact with systems that comply with them. Individuals from this subgroup wish to roll back virtually all existing data protection measures within healthcare in order to avoid situations in which their data will not be accessible to someone they want to share them with. They also celebrate the amalgamation of all personal healthcare data into one centralized source, as they believe it will enable their desired seamless, universal access. This article is based on twenty semi-structured interviews with members of the Danish public who were asked to comment on a big-data healthcare surveillance-driven project being developed in Denmark. My main questions here are: How can one define anti-privacy? What do anti-privacy attitudes in healthcare look like, and what is one of the routes that may lead to their adoption? Results show that a non-trivial minority of the interviewees displayed anti-privacy attitudes, which appear to have originated from frustrating healthcare data experiences over the last few years. The article concludes by discussing the possible proliferation of such anti-privacy sentiments, their implications, and by making recommendations regarding future information privacy policy.